Secrets of Borobudur Marathon: Tourism atraction, culture, brand image impact on purchase decisions - Chandra, David Kurnia; Widodo, Teguh; Ruspitasari, Widi Dewi (Manajemen Komunikasi, 2025)
Running has become a global phenomenon, including in Indonesia, with the number of runners tripling over the past few years. The Borobudur Marathon, which combines natural beauty and local culture, successfully attracts up to 10,000 runners annually. This study aims to analyze the impact of local culture and tourism attractions on purchase decisions among participants of the 2023 Borobudur Marathon, with brand image as a mediating variable. Adopting a quantitative approach, data were collected from 400 respondents using structured questionnaires and analyzed with SmartPLS 3.0 software. This study uses the Stimulus-Organism-Response (SOR) framework, considering tourism attraction and local culture as the stimuli, brand image as the organism, and purchase decision as a response. The results show that local culture and tourism attractions significantly enhance brand image, positively impacting purchase decisions. However, the direct relationship between local culture and purchase decisions was found to be insignificant, highlighting the critical role of brand image in shaping participant choices. These findings underscore the importance of leveraging local culture and tourism attractions to build a compelling brand image, fostering participant loyalty and engagement. For event organizers, these insights guide the development of strategic marketing approaches that enhance the overall participant experience. The study contributes to the theoretical understanding of the SOR and the dynamics between local culture, tourism attractions, brand image, and purchase decisions within the event object of sports tourism in the context of marketing communication. By applying these findings, organizers can create more memorable events.